Aspidistra jiangjinensis (Asparagaceae), a new species from Chongqing, China - Yi, Si-Yong; Huang, Ya; Chen, Hong-Yuan; Zhou, Xiao-Xu; Lin, Chun-Rui (Phytotaxa, 2020)
The genus Aspidistra Ker-Gawler (1822: t. 628) (Asparagaceae) is native to eastern and southeastern Asia and includes 170 species, of which more than 105 species occur in China (Liang & Tamura, 2000; Tillich, 2006, 2008, 2014; Averyanov et al. 2017, 2018, 2019; Lang et al. 1999; Li& Lin, 2016; Luo et al. 2018, Nong et al. 2018; Pan et al. 2019; Lin et al., 2019; Vislobokov et al. 2019a, 2019b). During a field trip in March 2019, an unusual species of Aspidistra with purple flowers was collected in Jiangjin District in southwest of Chongqing Municipality, China. After consulting herbarium specimens and relevant literature on Aspidistra, we reached the conclusion that the plant is a new species, here named Aspidistra jiangjinensis.